2017
DOI: 10.1038/srep42002
|View full text |Cite
|
Sign up to set email alerts
|

BIM-23A760 influences key functional endpoints in pituitary adenomas and normal pituitaries: molecular mechanisms underlying the differential response in adenomas

Abstract: Chimeric somatostatin/dopamine compounds such as BIM-23A760, an sst2/sst5/D2 receptors-agonist, have emerged as promising new approaches to treat pituitary adenomas. However, information on direct in vitro effects of BIM-23A760 in normal and tumoral pituitaries remains incomplete. The objective of this study was to analyze BIM-23A760 effects on functional parameters (Ca2+ signaling, hormone expression/secretion, cell viability and apoptosis) in pituitary adenomas (n = 74), and to compare with the responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 51 publications
(95 reference statements)
2
40
0
Order By: Relevance
“…The lack of glycemic side effects was confirmed in normal cynomolgous monkeys in which administration of BIM-23A760 produced potent, dose-related suppression of GH and IGF-1, but had no effect on either insulin secretion or circulating glucose. In addition to suppression of secretion, BIM-23A760 has been demonstrated to have potent antiproliferative effects, producing dose-related suppression of cultured primary human nonfunctioning pituitary adenoma cells ( Florio et al, 2008 ) and somatotropinoma cells ( Ibáñez-Costa et al, 2017a ). Furthermore, complete arrest of spontaneously developing, aggressive, nonfunctioning pituitary adenomas was observed in vivo in proopiomelanocortin KO mice, an effect not observed with pure SRIF or dopamine analogs, either alone or in combination.…”
Section: Multireceptor Somatotropin-release Inhibitory Factor Anamentioning
confidence: 99%
“…The lack of glycemic side effects was confirmed in normal cynomolgous monkeys in which administration of BIM-23A760 produced potent, dose-related suppression of GH and IGF-1, but had no effect on either insulin secretion or circulating glucose. In addition to suppression of secretion, BIM-23A760 has been demonstrated to have potent antiproliferative effects, producing dose-related suppression of cultured primary human nonfunctioning pituitary adenoma cells ( Florio et al, 2008 ) and somatotropinoma cells ( Ibáñez-Costa et al, 2017a ). Furthermore, complete arrest of spontaneously developing, aggressive, nonfunctioning pituitary adenomas was observed in vivo in proopiomelanocortin KO mice, an effect not observed with pure SRIF or dopamine analogs, either alone or in combination.…”
Section: Multireceptor Somatotropin-release Inhibitory Factor Anamentioning
confidence: 99%
“…Each pituitary sample subtype was evaluated by an expert anatomo-pathologist and confirmed by immunohistochemistry. Additionally, a molecular confirmation screening of relevant genes using quantitative real-time PCR was performed, as previously described [24][25][26][27]. In all cases, samples were placed in sterile cold medium (supplemented S-MEM, Gibco, Madrid, Spain) and dispersed into single cells following the methods and reagents previously described [24,26].…”
Section: Patients Tumor Samples and Primary Cell Culturesmentioning
confidence: 99%
“…To assess the effects of simvastatin on free cytosolic calcium kinetics, 50,000 cells/coverslip were plated and changes in (Ca 2+ ) i in single cells were measured using fura-2AM (Molecular Probes, Eugene, OR, USA), as described previously [25,26]. RNA Isolation, Reverse-Transcription, and Quantitative Real-Time PCR of Baboon Transcripts Primary pituitary cell cultures from baboons were processed for recovery of total RNA, subsequent quantification of RNA amount, reverse-transcription (RT), and application of a quantitative real-time PCR using kits, primers, and methods previously described [30].…”
Section: Measurement Of Free Cytosolic Calcium Concentration ([Ca 2+ mentioning
confidence: 99%
“…Specifically, the presence of the SSTR5-truncated isoforms has been correlated with a reduced response to SSA in GH-secreting tumours; for instance, sst5TMD4 was reported as particularly abundant in OCT-resistant somatotropinomas, suggesting its potential role in the attenuated response to SSA observed in some PT (83). The aryl hydrocarbon receptor-interacting protein (AIP) is another issue of interest, since several studies have observed how its low expression may be also associated with a worse response to SSA (81,84). B-arrestins, on their part, seem to affect the desensitization-internalization process of G-protein-coupled receptors, including SSTR, and they have been involved, for instance, in the recycling of SSTRs in GH-and PRL-secreting PT.…”
Section: Impaired Signal Transductionmentioning
confidence: 99%